Can Resonance Help to Analyze a Large Corpus of French Broadcast Homilies? - Emmanuel Dumont (International Journal of Homiletics)
The concept of resonance proposed by Hartmut Rosa offers a relational and bidirectional perspective, providing a valuable lens to address certain limitations of the concept of agency in theology. Specifically, it avoids emphasizing a stark opposition between human and divine agency. In this paper, we aimed to explore how preachers articulate a resonant relationship solely through the verbs they employ. Building on Anne Agersnap and Kirstine Helboe Johansen’s research on a corpus of Danish sermons, we conducted a distant reading of a substantial corpus comprising 2900 French broadcasted homilies. We applied a statistical approach to analyze the verbs present in this corpus, aiming to characterize the type of relationships that emerge from them. By applying a similar process to other types of biblical and secular texts, we were able to compare the relational dynamics that distinguish each corpus. This approach enhances our understanding of the literary genre of these homilies and situates their theological style within broader contexts.